EFEKTIVITAS SISTEM CONSTRUCTED WETLANDS KOMBINASI MELATI AIR (Echinodorus palaefolius) DAN KARBON AKTIF DALAM MENURUNKAN KADAR COD (Chemical Oxygen Demand) LIMBAH CAIR RUMAH SAKIT BANYUMANIK SEMARANG - Restu Andri Setiyanto; Yusniar Hanani Danudianti; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Medical liquid waste is all wastewater originating from the activities of the hospital and contains microorganisms, toxic chemicals, hazardous radioactive and other hazardous materials. Wastewater with high organic content can cause environmental pollution. Characteristics of high organic waste water shown by the high parameter Chemical Oxygen Demand (COD) in wastewater. High levels of COD can cause a decrease in dissolved oxygen in water. Then needed alternative biological sewage treatment systems which is a Constructed Wetlands System. This research aims to determine the effectiveness of the combined Constructed Wetlands system mexican sword plant and activated carbon to reduce the COD levels. The research is a quasi experimental study with pretest-posttest design with control group. The total sample is 48 sample which 32 treatment and 16 control samples. Anova test results with significant p-value <0.05 indicates that the treatment combined mexican sword plant and activated carbon and mexican sword plant treatment and control provide varying levels of COD. The average COD level before treatment was 86.18 mg/L, 86.95 mg/L, 87.66 mg/L. The precentage decreased levels of COD in control is 30,37%, and mexican sword plant treatment is 53.98% and combined of mexican sword plant and activated carbon treatment is 69.76%. Constructed Wetlands systems capability mexican sword plant and activated carbon have been effective in lowering COD levels of hospital wastewater because the result is already well below the standards based Central Java Provincial Regulation No. 5 in 2012 of 80 mg/L. Therefore, this system can be applied to hospital wastewater treatment.